Thermal aging resistant crosslinked polyethylene insulated power cable and preparation method thereof
Through multi-layer structure design and material combination, the aging problem of cross-linked polyethylene insulated power cables in high temperature and humid and heat environments is solved, and the stability and reliability of the cables are improved in harsh environments.
Patent Information
- Application Number
- CN202510466430.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2045-04-15
AI Technical Summary
The molecular chain of the cross-linked polyethylene insulated power cable breaks at high temperatures, resulting in a decline in mechanical strength and insulation performance. The hydrolysis reaction in the humid and hot environment accelerates the damage to the cross-linked structure. Frequent thermal cycles cause the material to shrink and expand repeatedly, resulting in fatigue crack propagation and interface bonding failure.
It adopts a multi-layer structural design, including an insulating layer, a fill layer, a composite functional layer and a sheath layer. It uses materials such as semiconductor crosslinked polyethylene, silicone resin, nanomontmorillonite, HALS light stabilizer, plasticized glass fiber cloth, rare earth oxide, thermal conductive layer, flame retardant layer and UV-resistant layer. Through thermal conductivity, flame retardant and UV-resistant collaborative design, combined with nanoTiO2 modification and segmented hot pressing roller composite technology, the interface chemical bonding is optimized to improve the material's thermal aging resistance.
It significantly improves the thermal stability and mechanical strength of the cable, extends the thermal aging time, reduces the material decomposition rate in humid and hot environments, and ensures the stability and reliability of the cable in high temperature, high humidity and frequent thermal cycle environments.
Smart Images

Figure CN120299811A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power cables, and specifically relates to a cross-linked polyethylene insulated power cable with heat aging resistance and a preparation method thereof. Background Art
[0002] Cross-linked polyethylene is a polymer commonly used as an insulating material for power cables. Its main advantages are excellent electrical properties and heat resistance, and it can maintain good insulation ability under high temperature and high pressure. Cross-linked polyethylene insulated power cables use chemical or physical methods to transform the polyethylene molecular structure from a linear molecular structure into a three-dimensional network structure, changing thermoplastic polyethylene into thermosetting cross-linked polyethylene, thereby improving the aging resistance, mechanical properties and environmental resistance of polyethylene, while maintaining excellent electrical properties, and having the advantages of light weight, simple structure, convenient use, chemical corrosion resistance and no laying drop limitation.
[0003] However, when cross-linked polyethylene is under high temperature (>90°C) for a long time, the C-H bonds and C-C bonds in the molecular chain will break due to thermal oxidation reaction, resulting in the gradual disintegration of the three-dimensional cross-linked network, and the decline of mechanical strength and insulation performance. In a humid and hot environment, the penetration of moisture accelerates the hydrolysis reaction of the material, destroys the cross-linked structure, further reduces the thermal stability, and frequent thermal cycling will also cause the material to shrink and expand repeatedly, leading to the propagation of fatigue cracks and the failure of interface adhesion. Summary of the Invention
[0004] In order to solve the above problems, the present invention provides a cross-linked polyethylene insulated power cable with heat aging resistance, which includes a conductor core, an insulating layer, a filling layer, a composite functional layer, a steel tape armor layer and a sheath layer from inside to outside;
[0005] The insulating layer is composed of semi-conductive cross-linked polyethylene, silicone resin, nano-montmorillonite and HALS light stabilizer in a mass ratio of 1: 0.2-0.3: 0.2-0.4: 0.08-0.1;
[0006] The filling layer is composed of plasticized fiberglass cloth, polyphenylene sulfide and rare earth oxide in a mass ratio of 1: 0.3-0.5: 0.05-0.08;
[0007] The composite functional layer includes a heat-conducting inner layer, a flame-retardant middle layer and an anti-UV outer layer from inside to outside in a layer thickness ratio of 0.1-0.3: 0.2-0.4: 0.05-0.1;
[0008] The sheath layer is composed of 25-35 parts of polyolefin, 9-12 parts of white carbon black, 10-15 parts of ceramized silicone rubber, 10-15 parts of flame retardant, 1-3 parts of polyethylene wax and 0.02-0.04 parts of initiator by weight.
[0009] Description: On the surface of the conductor covered by the semiconductive tape, the plasticizer silicone resin with higher thermal stability can avoid softening at high temperatures. The semiconductive cross-linked polyethylene can reduce partial discharge and improve the withstand voltage ability. The cross-linked polyethylene itself has good heat resistance. Nano-montmorillonite as a filler can increase the mechanical strength and barrier properties of the material, and delay thermal aging. The HALS light stabilizer is used to capture free radicals and prevent oxidation degradation caused by ultraviolet rays or heat. The combination of these materials can significantly improve the thermal aging resistance of the insulation layer; the plasticized fiberglass cloth is itself heat-resistant, and after adding polyphenylene sulfide, it can improve the heat resistance and flame retardancy of the filling layer. Rare earth oxides as stabilizers help the material maintain stability at high temperatures and delay aging. Such a filling layer may not only have thermal aging resistance, but also improve mechanical strength and flame retardancy; the heat-conducting layer may help dissipate heat, reduce the internal temperature of the cable, and reduce thermal aging; the flame-retardant layer improves the fire resistance; the anti-UV layer prevents ultraviolet degradation and is suitable for outdoor environments. The design of these three layers should comprehensively improve the environmental adaptability and long-term stability of the cable; polyolefin itself is chemically corrosion-resistant, white carbon black is used as a reinforcing agent, and the ceramized silicone rubber forms a ceramic protective layer at high temperatures to improve the fire resistance. The flame retardant decomposes endothermically and inhibits combustion. Polyethylene wax improves the processing performance, and the initiator is used for cross-linking reaction. Such a sheath has excellent flame retardancy, high temperature resistance, and mechanical protection.
[0010] Furthermore, the thickness ratio of the insulation layer, the filling layer, the composite functional layer, the steel tape armor layer, and the sheath layer is 1:1:1.5 - 2.5:1:2 - 3;
[0011] Description: The cable obtained with the above thickness ratio has a relatively stable structure and environmental adaptability.
[0012] Furthermore, the preparation method of the composite functional layer is as follows:
[0013] S1-1: Using polyolefin as the base material, adding 15 - 25% by mass of the thermal conductive filler based on the polyolefin, melting and blending the base material and the thermal conductive filler through a twin-screw extruder at a temperature of 180 - 200°C, controlling the shear rate at 300 - 600 rpm to uniformly disperse the filler, and forming a thermal conductive inner layer by the blown film method; the thermal conductive filler is composed of boron nitride and silane coupling agent in a ratio of 1:0.5 - 0.8;
[0014] S1-2: Using ethylene-vinyl acetate as the matrix, adding 30 - 40% by mass of the flame retardant based on the ethylene-vinyl acetate, drying at 95 - 105°C for 3.5 - 4.5 h and then extruding at a temperature of 200 - 220°C to obtain a flame retardant intermediate layer;
[0015] S1-3. Using thermoplastic polyurethane as the base material, adding 5-8% by mass of modified nano-TiO₂ and 2-3% by mass of silicone masterbatch based on the mass of the thermoplastic polyurethane, extruding at a temperature of 200-220 °C to obtain an anti-UV outer layer; after surface treatment, laminating with a flame-retardant intermediate layer and a heat-conducting inner layer successively through a hot press roller under the conditions of a pressure of 0.5-1.0 MPa and a temperature of 25-180 °C to obtain a composite functional layer;
[0016] Note: The composite functional layer is optimized by the synergistic design of heat conduction - flame retardancy - anti-UV and interfacial chemical bonding, significantly improving the thermal aging resistance. Boron nitride quickly conducts heat, avoiding thermal decomposition of the base material caused by local temperature rise. The silane coupling agent enhances the interfacial bonding between boron nitride and polyolefin, inhibiting stress cracking caused by the shedding of fillers at high temperatures. The silicone masterbatch improves the weather resistance and anti-humid heat aging ability of the outer layer, improves the melt fluidity of thermoplastic polyurethane, and reduces the molecular chain breakage caused by the processing heat history. The silane coupling agent modifies the surface of the heat-conducting filler, reducing the interfacial thermal resistance between the filler and the base material, and at the same time inhibiting the interlayer peeling caused by humid heat aging. Under long-term thermal aging at 150 °C or humid heat cycling, the mechanical property retention rate ≥ 85%, meeting the application requirements in harsh environments.
[0017] Further, the flame retardant is composed of aluminum hydroxide and zinc borate compounded at a mass ratio of 2-3:1;
[0018] Note: The compounding of aluminum hydroxide and zinc borate improves the high-temperature stability of the flame-retardant layer through the catalytic carbonization mechanism, achieving a flame-retardant effect.
[0019] Further, in S1-3, the preparation method of the modified nano-TiO₂ is as follows:
[0020] Dividing the nano-TiO₂ into 2-3 equal parts, taking one part and ultrasonically dispersing it with a silane coupling agent in ethanol at a mass ratio of 1:0.3 for 30 min, and drying to obtain the first modified TiO₂;
[0021] Taking the remaining 1-2 parts of nano-TiO₂, mica tape accounting for 5-8% by weight of the nano-TiO₂, and amino silane accounting for 0.5-2% by weight of the nano-TiO₂ for plasma treatment, with a treatment power of 45-50 W and a time of 50-60 s, to obtain the second modified TiO₂; mixing the first modified TiO₂ and the second modified TiO₂ in a ratio of 1:1 to obtain the modified nano-TiO₂;
[0022] Description: The methacryloxy groups of silane coupling agent KH-570 are combined with the hydroxyl groups on the surface of nano-TiO2 through hydrolysis to form a hydrophobic organic layer, reducing agglomeration and enhancing the compatibility with thermoplastic polyurethane. Ethanol ultrasonic dispersion further ensures the uniform distribution of the filler, avoiding the decrease in light scattering efficiency caused by local agglomeration. The amino functional groups of amino silane are combined with nano-TiO2 and mica tape through plasma activation to form a chemical bonding network. At the same time, the mica tape acts as a flaky support to inhibit the sedimentation of the filler; the first modified TiO2 scatters ultraviolet rays through its high refractive index, and the second modified TiO2 enhances the photocatalytic passivation ability through the surface defects activated by plasma. After mixing, a broad-spectrum UV shielding layer is formed. The hydrophobicity of KH-570 and the amino crosslinking effect of amino silane KH-550 cooperate to reduce the hydrolysis of the molecular chains of thermoplastic polyurethane in a humid and hot environment (85°C / 85% RH), maintaining long-term anti-UV performance. The step-by-step modification strategy optimizes through chemical bonding and regulates the physical structure to achieve the efficient functionalization of nano-TiO2 in the thermoplastic polyurethane substrate, providing high-reliability anti-UV performance and interface stability for the multi-layer composite structure; the combination of the enhanced rigidity of the first modified TiO2 and the flexible interface buffering of the second modified TiO2 enables the tensile strength of the outer layer of thermoplastic polyurethane to be ≥25 MPa and the elongation at break to be ≥400%.
[0023] Further, in S1-3, the method of surface treatment is: performing ultraviolet irradiation treatment on each layer interface, with the irradiation wavelength of 254-365 nm, the irradiation intensity of 50-100 mW / cm 2 , and the treatment time of 30-120 s;
[0024] Description: Using UV light to initiate the generation of free radicals on the TPU surface to promote the chemical bonding with the EVA flame-retardant layer.
[0025] Further, in S1-3, during the hot pressing roller lamination of the anti-UV outer layer and the flame-retardant intermediate layer, and the flame-retardant intermediate layer and the heat-conducting inner layer, a segmented lamination method is adopted,
[0026] The first stage: Pressurize under the conditions of 0.5 MPa and 180°C, with the pressure holding time of 15-30 s. Then, add epoxy-modified silicone resin accounting for 1-3 wt% of the thermoplastic polyurethane / olefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply a microwave-ultrasonic composite field treatment for 10-20 s, where the microwave power is 200-500 W and the ultrasonic frequency is 20-40 kHz;
[0027] The second stage: pressurize under the conditions of 1.0 MPa and 120 °C, with the pressure holding time being 15 - 30 s. During the pressure holding process, add 1 - 2 wt% of nano-silver antibacterial agent to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply microwave-ultrasonic composite field treatment for 15 - 25 s, where the microwave power is 100 - 300 W and the ultrasonic frequency is 15 - 30 kHz;
[0028] The third stage: pressurize under the conditions of 0.8 MPa and 25 - 30 °C, with the pressure holding time being 30 - 60 s.
[0029] Note: During the high-temperature interface bonding process in the first stage, the microwave treatment reduces the curing time of the epoxy resin by 30 - 50% compared with traditional heating, while the ultrasonic wave can eliminate the interface micropores and increase the peel strength by 15% - 20%. During the antibacterial agent dispersion process in the second stage, the ultrasonic cavitation effect makes the average particle size of nano-silver ≤ 50 nm, achieving the purpose of inhibiting the aggregation of nano-silver, and the microwave treatment can improve the uniformity of the nano-silver distribution without local enrichment, further making the antibacterial rate ≥ 99.9%. Finally, extending the pressure holding time in the low-temperature stage can release the residual stress and ensure the stability of the interlayer structure.
[0030] The present invention also provides a preparation method of a cross-linked polyethylene insulated power cable with anti-thermal aging performance, including the following steps:
[0031] S1. Take 3 - 5 copper wires and twist them together respectively to obtain 2 - 4 groups of conductor cores, and then mix, stir, degas, extrude and coat semi-conductive cross-linked polyethylene, silicone resin, nano-montmorillonite and HALS light stabilizer on the surface of the conductor cores to obtain an insulating layer;
[0032] S2. Then twist the conductor cores with insulating layers together, and mix, degas, extrude and fill plasticized fiberglass cloth, polyphenylene sulfide and rare earth oxide into the pores formed by the twisting of the conductor cores to obtain a filling layer;
[0033] S3. Coat an adhesive on the insulating layer and the filling layer and bond it with the composite functional layer, wind two layers of aluminized steel tapes outside the composite functional layer to obtain a steel tape armor layer, and finally wind a sheath layer outside the steel tape armor layer to obtain a power cable;
[0034] Note: Multiple copper wires are twisted together to form conductor cores. The plasticized fiberglass cloth is used to fill the gaps between the twisted conductors to improve the mechanical stress distribution. The semi-conductive cross-linked polyethylene forms a three-dimensional network structure through the cross-linking process, significantly improving the thermal stability. The nano-montmorillonite lamellar structure hinders the oxygen diffusion path and reduces the oxidation rate of the insulating layer. The rare earth oxide is cerium oxide, which can catalyze the decomposition of peroxides and inhibit the accumulation of high-temperature oxidation by-products.
[0035] Further, the adhesive is a silicone rubber-based adhesive;
[0036] Explanation: The silicone rubber-based adhesive has good heat resistance, weather resistance, flexibility, and electrical insulation properties.
[0037] Further, the initiator is dicumyl peroxide or bis(2,5-dimethyl-2,5-di(tert-butylperoxy)hexane);
[0038] Explanation: Dicumyl peroxide decomposes at high temperatures to generate free radicals, initiating the cross-linking of polyolefins and promoting the vulcanization of silicone rubber. Bis(2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) can reduce the risk of polyolefin thermal degradation and has good compatibility with polyethylene wax lubricants.
[0039] Compared with the existing technology, the beneficial effects of the present invention are:
[0040] (1) The power cable prepared by the present invention preferably uses cross-linked polyethylene and silicone resin as heat-resistant materials, and has multi-layer collaborative protection of heat conduction / flame retardancy / UV resistance / armoring. The heat-conducting inner layer quickly conducts the Joule heat of the conductor, avoiding local temperature rise and accelerating thermal aging; the flame-retardant intermediate layer delays heat transfer by endothermic decomposition and inhibits high-temperature combustion; the aluminized steel tape armor layer reflects external radiant heat, and the double-layer winding structure improves the mechanical barrier performance, reducing the damage of thermal stress to internal materials; achieving a comprehensive improvement in thermal aging resistance performance and being suitable for harsh environments of high temperature, high humidity, and frequent thermal cycling.
[0041] (2) The present invention divides TiO2 into two parts, which are treated with different coupling agents and plasma respectively. The first part is treated with a silane coupling agent, and the second part is treated with an amino silane and plasma, and then mixed and used for the UV-resistant layer of thermoplastic polyurethane; the silane coupling agent can provide compatibility with thermoplastic polyurethane, and the amino group of the amino silane can form a stronger physical bond with the flame-retardant intermediate layer after plasma treatment, realizing the efficient functionalization of nano-TiO2 in the TPU substrate and providing high-reliability UV resistance performance and interface stability for the multi-layer composite structure; the combination of the enhanced rigidity of the first modified TiO2 and the flexible interface buffer of the second modified TiO2 enhances both the tensile strength and elongation at break of the thermoplastic polyurethane outer layer, thereby optimizing the performance of the power cable. Description of the Drawings
[0042] Figure 1 is a comparison chart of the thermal aging resistance performance of the cross-linked polyethylene insulated power cables of Examples 1 to 11 and Control Groups 1 to 2 of the present invention;
[0043] Figure 2 is a comparison chart of the tensile strength of the cross-linked polyethylene insulated power cables of Examples 1 to 11 and Control Groups 1 to 2 of the present invention;
[0044] Figure 3It is a comparison chart of the stripping strength retention rates of cross-linked polyethylene insulated power cables in Examples 1 to 11 and Control Groups 1 to 2 of the present invention;
[0045] Figure 4 It is a comparison chart of the thermal aging resistance performance of cross-linked polyethylene insulated power cables in Examples 1, 11 to 15 and Control Groups 3 to 4 of the present invention;
[0046] Figure 5 It is a comparison chart of the tensile strength of cross-linked polyethylene insulated power cables in Examples 1, 11 to 15 and Control Groups 3 to 4 of the present invention;
[0047] Figure 6 It is a comparison chart of the stripping strength retention rates of cross-linked polyethylene insulated power cables in Examples 1, 11 to 15 and Control Groups 3 to 4 of the present invention;
[0048] Figure 7 It is a comparison chart of the thermal aging resistance performance of cross-linked polyethylene insulated power cables in Examples 1, 16 to 22 of the present invention;
[0049] Figure 8 It is a comparison chart of the tensile strength of cross-linked polyethylene insulated power cables in Examples 1, 16 to 22 of the present invention;
[0050] Figure 9 It is a comparison chart of the stripping strength retention rates of cross-linked polyethylene insulated power cables in Examples 1, 16 to 22 of the present invention. Detailed implementation manners
[0051] To further elaborate on the methods adopted and the effects achieved by the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with experiments.
[0052] Example 1: A cross-linked polyethylene insulated power cable with thermal aging resistance, which includes a conductor core, an insulating layer, a filling layer, a composite functional layer, a steel tape armor layer and a sheath layer from the inside to the outside;
[0053] The insulating layer is composed of semiconductive cross-linked polyethylene, silicone resin, nano-montmorillonite and HALS light stabilizer in a mass ratio of 1:0.25:0.3:0.09;
[0054] The filling layer is composed of plasticized fiberglass cloth, polyphenylene sulfide and rare earth oxide in a mass ratio of 1:0.4:0.06; the rare earth oxide is cerium oxide;
[0055] The composite functional layer includes a heat-conducting inner layer, a flame-retardant intermediate layer and an anti-UV outer layer in sequence from the inside to the outside, and the thickness ratio between layers is 0.2:0.3:0.07;
[0056] The sheath layer is composed of 30 parts of polyolefin, 10 parts of silica, 13 parts of ceramized silicone rubber, 13 parts of flame retardant, 2 parts of polyethylene wax, and 0.03 parts of initiator by weight; the initiator is dicumyl peroxide;
[0057] The thickness ratio of the insulation layer, filling layer, composite functional layer, steel tape armor layer, and sheath layer is 1:1:2:1:2.5;
[0058] The preparation method of the composite functional layer is as follows:
[0059] S1-1: Using polyolefin as the base material, adding 20% by mass of the heat-conducting filler based on the mass of polyolefin, melting and blending the base material and the heat-conducting filler through a twin-screw extruder at a temperature of 190 °C, controlling the shear rate at 450 rpm to uniformly disperse the filler, and forming a heat-conducting inner layer by the blown film method; the heat-conducting filler is composed of boron nitride and silane coupling agent in a ratio of 1:0.7;
[0060] S1-2: Using ethylene-vinyl acetate as the matrix, adding 35% by mass of the flame retardant based on the mass of ethylene-vinyl acetate, drying at 411 °C for 4 h and then extruding at a temperature of 210 °C to obtain a flame-retardant intermediate layer; the flame retardant is composed of aluminum hydroxide and zinc borate compounded in a mass ratio of 2.5:1;
[0061] S1-3: Using thermoplastic polyurethane as the base material, adding 7% by mass of modified nano-TiO2 and 2.5% by mass of silicone masterbatch based on the mass of thermoplastic polyurethane, and extruding at a temperature of 210 °C to obtain an anti-UV outer layer; after surface treatment, it is compounded with the flame-retardant intermediate layer and the heat-conducting inner layer in sequence through a hot press roller under the conditions of a pressure of 0.8 MPa and a temperature of 150 °C to obtain a composite functional layer; the surface treatment method is: performing ultraviolet light irradiation treatment between layers, with an irradiation wavelength of 288 nm and an irradiation intensity of 75 mW / cm 2 , and the treatment time is 80 s; in this embodiment, the modified nano-TiO2 is obtained by mixing with a silane coupling agent in a mass ratio of 1:0.3 and adding it to ethanol with a mass concentration of 95% in a volume ratio of 1:8 for dispersion;
[0062] A preparation method of a heat-aging-resistant cross-linked polyethylene insulated power cable includes the following steps:
[0063] S1: Take 4 copper wires and twist them together to obtain 3 groups of conductor cores, and then knead, stir, defoam, extrude, and coat semi-conductive cross-linked polyethylene, silicone resin, nano-montmorillonite, and HALS light stabilizer on the surface of the conductor cores to obtain an insulation layer;
[0064] S2. Then, twist the conductor cores with insulating layers in each group together, and knead, degas, extrude, and fill the plasticized fiberglass cloth, polyphenylene sulfide, and rare earth oxide into the pores formed by the twisted conductor cores to obtain a filling layer;
[0065] S3. Coat a silicone rubber-based adhesive on the insulating layer and the filling layer and bond them to the composite functional layer. Wrap two layers of aluminized steel tapes around the composite functional layer to obtain a steel tape armor layer. Finally, wrap the sheath layer around the steel tape armor layer to obtain a power cable.
[0066] Example 2: Different from Example 1, the insulating layer is composed of semiconductive crosslinked polyethylene, silicone resin, nano-montmorillonite, and HALS light stabilizer in a mass ratio of 1:0.2:0.2:0.08.
[0067] Example 3: Different from Example 1, the insulating layer is composed of semiconductive crosslinked polyethylene, silicone resin, nano-montmorillonite, and HALS light stabilizer in a mass ratio of 1:0.3:0.4:0.1.
[0068] Example 4: Different from Example 1, the filling layer is composed of plasticized fiberglass cloth, polyphenylene sulfide, and rare earth oxide in a mass ratio of 1:0.3:0.05.
[0069] Example 5: Different from Example 1, the filling layer is composed of plasticized fiberglass cloth, polyphenylene sulfide, and rare earth oxide in a mass ratio of 1:0.5:0.08.
[0070] Example 6: Different from Example 1, the layer thickness ratio is 0.1:0.2:0.05.
[0071] Example 7: Different from Example 1, the layer thickness ratio is 0.3:0.4:0.1.
[0072] Example 8: Different from Example 1, the sheath layer is composed of, by weight, 25 parts of polyolefin, 9 parts of white carbon black, 10 parts of ceramizable silicone rubber, 10 parts of flame retardant, 1 part of polyethylene wax, and 0.02 part of initiator.
[0073] Example 9: Different from Example 1, the sheath layer is composed of, by weight, 35 parts of polyolefin, 12 parts of white carbon black, 15 parts of ceramizable silicone rubber, 15 parts of flame retardant, 3 parts of polyethylene wax, and 0.04 part of initiator.
[0074] Example 10: Different from Example 1, the thickness ratio of the insulating layer, the filling layer, the composite functional layer, the steel tape armor layer, and the sheath layer is 1:1:1.5:1:2.
[0075] Example 11: Different from Example 1, the thickness ratio of the insulation layer, the filling layer, the composite functional layer, the steel tape armor layer and the sheath layer is 1:1:2.5:1:3.
[0076] Example 12: Different from Example 1, the preparation method of the composite functional layer is as follows:
[0077] S1-1: Using polyolefin as the base material, adding 15% by mass of the heat-conducting filler based on the polyolefin, melting and blending the base material and the heat-conducting filler through a twin-screw extruder at a temperature of 180 °C, controlling the shear rate at 300 rpm to uniformly disperse the filler, and forming a heat-conducting inner layer by the blown film method; the heat-conducting filler is composed of boron nitride and silane coupling agent in a ratio of 1:0.5;
[0078] S1-2: Using ethylene-vinyl acetate as the matrix, adding 30% by mass of the flame retardant based on the ethylene-vinyl acetate, drying at 95 °C for 3.5 h and then extruding at a temperature of 200 °C to obtain a flame-retardant intermediate layer;
[0079] S1-3: Using thermoplastic polyurethane as the base material, adding 5% by mass of modified nano-TiO2 and 2% by mass of silicone masterbatch based on the thermoplastic polyurethane, and extruding at a temperature of 200 °C to obtain an anti-UV outer layer; after surface treatment, it is laminated with the flame-retardant intermediate layer and the heat-conducting inner layer in sequence through a hot press roller under the conditions of a pressure of 0.5 MPa and a temperature of 25 °C to obtain a composite functional layer; the surface treatment method is: performing ultraviolet light irradiation treatment between layers, with an irradiation wavelength of 254 nm and an irradiation intensity of 50 mW / cm 2 , and the treatment time is 30 s.
[0080] Example 13: Different from Example 1, the preparation method of the composite functional layer is as follows:
[0081] S1-1: Using polyolefin as the base material, adding 25% by mass of the heat-conducting filler based on the polyolefin, melting and blending the base material and the heat-conducting filler through a twin-screw extruder at a temperature of 200 °C, controlling the shear rate at 600 rpm to uniformly disperse the filler, and forming a heat-conducting inner layer by the blown film method; the heat-conducting filler is composed of boron nitride and silane coupling agent in a ratio of 1:0.8;
[0082] S1-2: Using ethylene-vinyl acetate as the matrix, adding 40% by mass of the flame retardant based on the ethylene-vinyl acetate, drying at 105 °C for 4.5 h and then extruding at a temperature of 220 °C to obtain a flame-retardant intermediate layer;
[0083] S1-3: Using thermoplastic polyurethane as the base material, adding 8% by mass of modified nano-TiO₂ and 3% by mass of silicone masterbatch based on the mass of thermoplastic polyurethane, extruding at a temperature of 220 °C to obtain an anti-UV outer layer; after surface treatment, it is successively compounded with a flame-retardant intermediate layer and a heat-conducting inner layer through a hot press roller under the conditions of a pressure of 1.0 MPa and a temperature of 180 °C to obtain a composite functional layer; the method of surface treatment is: performing ultraviolet irradiation treatment between layers, with an irradiation wavelength of 365 nm and an irradiation intensity of 100 mW / cm 2 , and the treatment time is 120 s.
[0084] Example 14: Different from Example 1, in S1-2, the flame retardant is composed of aluminum hydroxide and zinc borate compounded according to a mass ratio of 2:1.
[0085] Example 15: Different from Example 1, in S1-2, the flame retardant is composed of aluminum hydroxide and zinc borate compounded according to a mass ratio of 3:1.
[0086] Example 16: Different from Example 1, in S1-3, the preparation method of the modified nano-TiO₂ is as follows:
[0087] Divide the nano-TiO₂ into two equal parts, take one part and mix it with a silane coupling agent according to a mass ratio of 1:0.3, then add it to ethanol with a concentration of 95% according to a ratio of 1 g:8 mL and ultrasonically disperse for 30 min, and dry to obtain the first modified TiO₂;
[0088] Take the remaining one part of nano-TiO₂, mica tape accounting for 7% of the weight of nano-TiO₂, and amino silane accounting for 1.2% of the weight of nano-TiO₂ for plasma treatment, with a treatment power of 48 W and a time of 55 s to obtain the second modified TiO₂; mix the first modified TiO₂ and the second modified TiO₂ in a ratio of 1:1 to obtain the modified nano-TiO₂.
[0089] Example 17: Different from Example 16, in S1-3, the preparation method of the modified nano-TiO₂ is as follows:
[0090] Divide the nano-TiO₂ into two equal parts, take one part and mix it with a silane coupling agent according to a mass ratio of 1:0.3, then add it to ethanol with a concentration of 95% according to a ratio of 1 g:5 mL and ultrasonically disperse for 30 min, and dry to obtain the first modified TiO₂;
[0091] Take the remaining one part of nano-TiO₂, mica tape accounting for 5% of the weight of nano-TiO₂, and amino silane accounting for 0.5% of the weight of nano-TiO₂ for plasma treatment, with a treatment power of 45 W and a time of 50 s to obtain the second modified TiO₂; mix the first modified TiO₂ and the second modified TiO₂ in a ratio of 1:1 to obtain the modified nano-TiO₂.
[0092] Example 18: Different from Example 16, in S1-3, the preparation method of the modified nano-TiO₂ is as follows:
[0093] The nano-TiO₂ is divided into three equal parts. One part is mixed with a silane coupling agent at a mass ratio of 1:0.3, and then added to ethanol with a concentration of 95% according to a ratio of 1 g:10 mL and ultrasonically dispersed for 30 min. After drying, the first modified TiO₂ is obtained;
[0094] Take the remaining two parts of nano-TiO₂, mica tape accounting for 8% of the weight of nano-TiO₂, and amino silane accounting for 2% of the weight of nano-TiO₂ for plasma treatment. The treatment power is 50 W and the time is 60 s to obtain the second modified TiO₂; The first modified TiO₂ and the second modified TiO₂ are mixed in a ratio of 1:1 to obtain the modified nano-TiO₂.
[0095] Example 19: Different from Example 16, in S1-3, during the hot roll lamination of the anti-UV outer layer and the flame-retardant intermediate layer, and the flame-retardant intermediate layer and the heat-conducting inner layer, segmented lamination is used.
[0096] First stage: Pressurize under the conditions of 0.5 MPa and 180 °C, and the pressure holding time is 22 s. Then, add epoxy-modified silicone resin accounting for 3 wt% of the thermoplastic polyurethane / olefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply a microwave-ultrasonic composite field treatment for 15 s, where the microwave power is 350 W and the ultrasonic frequency is 30 kHz;
[0097] Second stage: Pressurize under the conditions of 1.0 MPa and 120 °C, and the pressure holding time is 22 s. During the pressure holding process, add nano-silver antibacterial agent accounting for 1.5 wt% of the thermoplastic polyurethane / olefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply a microwave-ultrasonic composite field treatment for 20 s, where the microwave power is 200 W and the ultrasonic frequency is 22 kHz;
[0098] Third stage: Pressurize under the conditions of 0.8 MPa and 25 - 30 °C, and the pressure holding time is 45 s.
[0099] Example 20: Different from Example 19, in S1-3, during the hot roll lamination of the anti-UV outer layer and the flame-retardant intermediate layer, and the flame-retardant intermediate layer and the heat-conducting inner layer, segmented lamination is used.
[0100] The first stage: pressurize under the conditions of 0.5 MPa and 180 °C, with a pressure holding time of 15 s. Then, add epoxy-modified silicone resin accounting for 1 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply microwave-ultrasonic composite field treatment for 10 s, where the microwave power is 200 W and the ultrasonic frequency is 20 kHz;
[0101] The second stage: pressurize under the conditions of 1.0 MPa and 120 °C, with a pressure holding time of 15 s. During the pressure holding process, add nano-silver antibacterial agent accounting for 1 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply microwave-ultrasonic composite field treatment for 15 s, where the microwave power is 100 W and the ultrasonic frequency is 15 kHz;
[0102] The third stage: pressurize under the conditions of 0.8 MPa and 25 °C, with a pressure holding time of 30 s.
[0103] Example 21: Different from Example 19, in S1-3, segmented lamination is adopted during the hot-roll lamination process between the anti-UV outer layer and the flame-retardant intermediate layer, and between the flame-retardant intermediate layer and the heat-conducting inner layer.
[0104] The first stage: pressurize under the conditions of 0.5 MPa and 180 °C, with a pressure holding time of 30 s. Then, add epoxy-modified silicone resin accounting for 3 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply microwave-ultrasonic composite field treatment for 20 s, where the microwave power is 500 W and the ultrasonic frequency is 40 kHz;
[0105] The second stage: pressurize under the conditions of 1.0 MPa and 120 °C, with a pressure holding time of 30 s. During the pressure holding process, add nano-silver antibacterial agent accounting for 2 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply microwave-ultrasonic composite field treatment for 25 s, where the microwave power is 300 W and the ultrasonic frequency is 30 kHz;
[0106] The third stage: pressurize under the conditions of 0.8 MPa and 30 °C, with a pressure holding time of 60 s.
[0107] Example 22: Different from Example 19, the initiator is bis(2,5-dimethyl-2,5-di(tert-butylperoxy)hexane).
[0108] Experimental example: The narrative basis of this experimental example is the recording scheme in Example 1, aiming to clarify the actual application effect of the present invention. The power cables obtained in each example are tested for thermal aging resistance, tensile strength, and damp heat cycling. The average value of the test results of three times for each example is taken as the final test result, and the following is explored:
[0109] Performance tests were carried out on the power cables obtained from Examples 1 to 22 respectively. Thermal stability time test: Test samples were made according to GB / T2951.11-2008 and placed on a clean glass plate. When the temperature of the thermal aging test chamber was raised to 200°C, the glass plate was quickly placed into it. When the temperature reached 200°C, timing started. Observe the color change carefully. The time required when the color began to turn slightly yellow was recorded as the thermal stability time at 200°C.
[0110] Damp heat cycle test (-40°C to 85°C / 85% RH, cycle 100 times) was carried out to verify the interlayer bonding stability, i.e., the retention rate of peel strength. The test results are as follows:
[0111] 1. Explore the influence of component composition on the performance of cross-linked polyethylene insulated power cables
[0112] Control group 1: Different from Example 1, silicone resin was not added to the insulating layer.
[0113] Control group 2: Different from Example 1, rare earth oxides were not included in the filling layer.
[0114] Conclusion: From the comparison of Example 1 to Example 3 and Control group 1, it can be seen that not adding silicone resin will cause a decrease in the thermal aging resistance, tensile strength and retention rate of peel strength of the power cable. This is because the thermal decomposition rate of the insulating layer lacking silicone resin increases at high temperatures above 90°C, and the retention rate of the elongation at break of cross-linked polyethylene will decrease from ≥80% to ≤60%. At the same time, HALS migrates and fails quickly due to the lack of a fixed carrier, and the interfacial microcracks cannot be effectively repaired, resulting in a reduction in the thermal stability time. The toughening effect of silicone resin is missing, and the retention rate of the tensile strength of the insulating layer decreases with the increase of thermal aging time. And due to the insufficient interfacial bonding force of nano-montmorillonite, the lamellar peeling is likely to occur, resulting in a decrease in the tensile strength. At the same time, due to the strong fluidity of silicone resin, it can penetrate into the interfacial microcracks of the composite material, thus enhancing the interlayer bonding strength and increasing the peel strength by about 20%.
[0115] From the comparison of Example 1, Examples 4 to 5 and Control Group 2, it can be seen that the absence of rare earth oxides will also cause a decrease in the thermal aging resistance, tensile strength and peel strength retention rate of the power cable. This is because rare earth oxides have a catalytic carbonization effect, which can improve the thermal stability of polyphenylene sulfide at high temperatures with a thermal decomposition temperature ≥ 200 °C. When rare earth oxides are lacking, the thermal oxidation rate of the filling layer accelerates at temperatures above 200 °C, and the thermal stability time is shortened by ≥ 30%; rare earth oxides can improve the interfacial compatibility between the plasticized fiberglass cloth and polyphenylene sulfide. After the absence, fiber-resin debonding easily occurs inside the filling layer, and the tensile strength decreases by ≥ 15%; at the same time, rare earth oxides can inhibit the hydrolysis reaction of polyphenylene sulfide in a humid and hot environment. When absent, the interface between the filling layer and the adjacent layer swells due to water absorption, resulting in the peel strength retention rate decreasing from ≥ 80% to ≤ 60%.
[0116] 2. Explore the influence of the preparation method of the composite functional layer on the performance of cross-linked polyethylene insulated power cables
[0117] Control Group 3: Different from Example 1, the surface treatment uses the plasma treatment method, with a treatment power of 75 W and a time of 60 s.
[0118] Control Group 4: Different from Example 1, no silicone masterbatch is added during the preparation of the anti-UV outer layer.
[0119] Conclusion: From the comparison of Example 1, Examples 12 to 15 and Control Group 3 and Control Group 4, it can be seen that replacing the ultraviolet light irradiation treatment with the plasma treatment method and not adding silicone masterbatch during the preparation of the anti-UV outer layer will both cause a decline in the performance of the composite functional layer. This is because high-intensity ultraviolet light irradiation can optimize the dispersion of nano-TiO2 and the silicone masterbatch, and improve the interfacial shear strength between the fiber and the substrate. Although the plasma treatment increases the surface roughness, it only forms a physical bond, and the increase in the interfacial shear strength is relatively low and it is prone to failure due to the humid and hot environment; ultraviolet light induces the formation of covalent bonds between the Si-O bonds in the silicone masterbatch and the TPU substrate, and the peel strength retention rate is ≥ 80% after wet heat aging. The plasma treatment relies on physical adsorption, and the interface is prone to water absorption and swelling in the humid and hot environment, resulting in a significant decrease in the peel strength retention rate; while not adding silicone masterbatch during the preparation of the anti-UV outer layer will cause the interface between the TPU and the flame-retardant intermediate layer to be loosely combined due to the absence of the silicone masterbatch, the oxygen permeability increases, and the thermal stability time is reduced by ≥ 20%. When not added, the uneven distribution of nanoparticles causes microcracks, and the tensile strength decreases by ≥ 18%. When not added, the interface relies on physical adsorption, and the peel strength retention rate decreases by ≥ 30% after wet heat aging.
[0120] 3. Explore the influence of the composite method of modified nano-TiO2 and the hot pressing roller on the performance of cross-linked polyethylene insulated power cables
[0121] Conclusion: From the comparison of Examples 1, 16 to 18, it can be seen that the preparation method of the modified nano-TiO2 of the present application has a positive impact on improving the performance of cross-linked polyethylene insulated power cables. Specifically, the first modified TiO2 modified by the silane coupling agent forms a dense coating layer through the hydrophobic groups (such as -CH3) of the silane coupling agent, reducing the penetration of moisture and oxygen, inhibiting the thermal oxidation decomposition of the substrate at high temperatures. The synergistic effect of the mica tape and plasma treatment in the second modified TiO2 forms a multi-layer heat insulation structure in the cable insulation layer, delaying heat transfer and extending the thermal stability time; the lamellar structure of the mica tape is combined with the amino silane through plasma treatment, and the tensile strength is improved after being embedded in the substrate; the hydrophobicity of the amino silane and the layered structure of the mica tape act synergistically to reduce the water absorption rate at the cable interface, and the retention rate of the peel strength after damp heat aging is also significantly improved.
[0122] From the comparison of Examples 16, 19 to 22, it can be seen that the segmented mixing can further improve the thermal aging resistance, tensile properties and retention rate of peel strength of cross-linked polyethylene insulated power cables. Considering comprehensively, Example 19 is the optimal solution.
Claims
1. A cross-linked polyethylene insulated power cable resistant to heat aging, characterized in that, From the inside to the outside, it includes a conductor core, an insulating layer, a filling layer, a composite functional layer, a steel tape armor layer, and a sheath layer; The insulating layer is composed of semiconductive cross-linked polyethylene, silicone resin, nano-montmorillonite, and HALS light stabilizer in a mass ratio of 1: 0.2 - 0.3: 0.2 - 0.4: 0.08 - 0.1; The filling layer is composed of plasticized fiberglass cloth, polyphenylene sulfide, and rare earth oxide in a mass ratio of 1: 0.3 - 0.5: 0.05 - 0.08; The composite functional layer sequentially includes a heat-conducting inner layer, a flame-retardant intermediate layer, and an anti-UV outer layer from the inside to the outside, and the thickness ratio between layers is 0.1 - 0.3: 0.2 - 0.4: 0.05 - 0.1; The sheath layer is composed of 25 - 35 parts by weight of polyolefin, 9 - 12 parts of white carbon black, 10 - 15 parts of ceramizable silicone rubber, 10 - 15 parts of flame retardant, 1 - 3 parts of polyethylene wax, and 0.02 - 0.04 parts of initiator according to weight parts.
2. The cross-linked polyethylene insulated power cable with heat aging resistance as described in claim 1, characterized in that, The thickness ratio of the insulating layer, the filling layer, the composite functional layer, the steel tape armor layer, and the sheath layer is 1: 1: 1.5 - 2.5: 1: 2 - 3.
3. The cross-linked polyethylene insulated power cable with heat aging resistance according to claim 2, characterized in that, The preparation method of the composite functional layer is as follows: S1-1: Using polyolefin as the base material, adding 15 - 25% of the mass of the polyolefin as the heat-conducting filler, melting and blending the base material and the heat-conducting filler through a twin-screw extruder at a temperature of 180 - 200 °C, controlling the shear rate to be 300 - 600 rpm to uniformly disperse the filler, and forming a heat-conducting inner layer by the blown film method; the heat-conducting filler is composed of boron nitride and silane coupling agent in a ratio of 1: 0.5 - 0.8; S1-2: Using ethylene-vinyl acetate as the matrix, adding 30 - 40% of the mass of the ethylene-vinyl acetate as the flame retardant, drying at 95 - 105 °C for 3.5 - 4.5 h and then extruding at a temperature of 200 - 220 °C to obtain a flame-retardant intermediate layer; S1-3: Using thermoplastic polyurethane as the base material, adding 5 - 8% of the mass of the thermoplastic polyurethane as the modified nano-TiO2 and 2 - 3% of the mass of the thermoplastic polyurethane as the silicone masterbatch, extruding at a temperature of 200 - 220 °C to obtain an anti-UV outer layer; after surface treatment, it is compounded with the flame-retardant intermediate layer and the heat-conducting inner layer in sequence through a hot press roller under the conditions of a pressure of 0.5 - 1.0 MPa and a temperature of 25 - 180 °C to obtain a composite functional layer.
4. The cross-linked polyethylene insulated power cable with heat aging resistance according to claim 3, characterized in that The flame retardant is composed of aluminum hydroxide and zinc borate compounded in a mass ratio of 2 - 3:
1.
5. The cross-linked polyethylene insulated power cable with heat aging resistance according to claim 3, characterized in that, In S1-3, the preparation method of the modified nano-TiO2 is as follows: Dividing the nano-TiO2 into 2 - 3 equal parts, taking one part and ultrasonically dispersing it in ethanol with a silane coupling agent at a mass ratio of 1: 0.3 for 30 min, and drying to obtain the first modified TiO2; Taking the remaining 1 - 2 parts of nano-TiO2, 5 - 8% of the weight of the nano-TiO2 as mica tape, and 0.5 - 2% of the weight of the nano-TiO2 as amino silane for plasma treatment, with a treatment power of 45 - 50 W and a time of 50 - 60 s to obtain the second modified TiO2; mixing the first modified TiO2 and the second modified TiO2 in a ratio of 1: 1 to obtain the modified nano-TiO2.
6. The cross-linked polyethylene insulated power cable with heat aging resistance according to claim 2, wherein In S1-3, the surface treatment method is: performing ultraviolet irradiation treatment between layers, with an irradiation wavelength of 254 - 365 nm, an irradiation intensity of 50 - 100 mW / cm 2 , and a treatment time of 30 - 120 s.
7. The cross-linked polyethylene insulated power cable with heat aging resistance as described in claim 2, wherein In S1-3, a segmented composite method is adopted during the hot roll lamination of the anti-UV outer layer with the flame-retardant intermediate layer and the flame-retardant intermediate layer with the heat-conducting inner layer. The first stage: Pressurize under the conditions of 0.5 MPa and 180 °C, with a pressure holding time of 15 - 30 s. Then, add epoxy-modified silicone resin accounting for 1 - 3 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply a microwave-ultrasonic composite field treatment for 10 - 20 s, where the microwave power is 200 - 500 W and the ultrasonic frequency is 20 - 40 kHz. The second stage: Pressurize under the conditions of 1.0 MPa and 120 °C, with a pressure holding time of 15 - 30 s. During the pressure holding process, add nano-silver antibacterial agent accounting for 1 - 2 wt% of the thermoplastic polyurethane / polyolefin substrate to the contact surface between the anti-UV outer layer and the flame-retardant intermediate layer / the contact surface between the flame-retardant intermediate layer and the heat-conducting inner layer, and apply a microwave-ultrasonic composite field treatment for 15 - 25 s, where the microwave power is 100 - 300 W and the ultrasonic frequency is 15 - 30 kHz. The third stage: Pressurize under the conditions of 0.8 MPa and 25 - 30 °C, with a pressure holding time of 30 - 60 s.
8. The preparation method of a cross-linked polyethylene insulated power cable with heat aging resistance according to any one of claims 1 to 7, characterized in that, It includes the following steps: S1: Take 3 - 5 copper wires and twist them together respectively to obtain 2 - 4 groups of conductor cores. Then, mix, stir, degas, extrude and coat the semi-conductive cross-linked polyethylene, silicone resin, nano-montmorillonite and HALS light stabilizer on the surface of the conductor cores to obtain an insulating layer. S2: Then twist the conductor cores with insulating layers of each group together, and mix, degas, extrude and fill the plasticized fiberglass cloth, polyphenylene sulfide and rare earth oxides into the pores formed by the twisting of the conductor cores to obtain a filling layer. S3: Coat an adhesive on the insulating layer and the filling layer and bond them with the composite functional layer. Wind two layers of aluminized steel tapes outside the composite functional layer to obtain a steel tape armor layer. Finally, wind a sheath layer outside the steel tape armor layer to obtain a power cable.
9. The preparation method of a cross-linked polyethylene insulated power cable resistant to heat aging according to claim 8, characterized in that, The adhesive is a silicone rubber-based adhesive.
10. The preparation method of a cross-linked polyethylene insulated power cable resistant to thermal aging according to claim 1, characterized in that, The initiator is dicumyl peroxide or bis(2,5-dimethyl-2,5-di(tert-butylperoxy)hexane).
Citation Information
Patent Citations
Cable sheath with high corrosion resistance and weather resistance
CN105524427A
Photoelectric composite flexible cable and production extrusion equipment and preparation method thereof
CN112259282A
Aerial insulated cable
CN206806069U
Low-temperature-resistant tensile charging pile cable
CN213904989U
An electric and / or optical cable
GB2101392A
Cited By
Anti-freezing, anti-cracking and cold-resistant cable
CN120600395A
Crosslinked insulated cable and preparation method thereof
CN121617710A
A crosslinked insulated cable and a method for producing the same
CN121617710B